Vector Basis {(1,1,1,1), (1,1,1,0), (1,1,0,0), (1,0,0,0)}-Cordial Labeling of D(T_n)mK_1 and D(Q_n)mK_1 - R. Ponraj; R. Jeya (International Journal of Mathematics And its Applications, 2025)
Let G be a (p,q) graph. Let V be an inner product space with basis S. We denote the inner product of the vectors x and y by <x,y>. Let φ: V(G) → S be a function. For edge uv assign the label <φ(u),φ(v)>. Then φ is called a vector basis S-cordial labeling of G if |φ_x-φ_y|≤ 1 and |γ_i-γ_j |≤ 1 where φ_x denotes the number of vertices labeled with the vector x and γ_i denotes the number of edges labeled with the scalar i. A graph which admits a vector basis S-cordial labeling is called a vector basis S-cordial graph. In this paper, we prove that the graphs D(T_n)mK_1 and D(Q_n)mK_1 admit a vector basis {(1,1,1,1),(1,1,1,0),(1,1,0,0),(1,0,0,0)}-cordial.